Genome-Wide Identification and Characterization of the Potato IQD Family During Development and Stress - Mei, Chao; Liu, Yuwei; Dong, Xue; Song, Qianna; Wang, Huijie; Shi, Hongwei; Feng, Ruiyun (Frontiers in Genetics, 2021)
Calmodulin-binding proteins (CaMBPs) belong to the IQ67 domain (IQD) gene family and play essential roles in plant development and stress responses. However, the role of IQD gene family in potato (Solanum tuberosum L.)is yet to be known. In the present study, 23 StIQDs were identified in the potato genome and named StIQD1 to StIQD23. They were unevenly distributed on 10 of the 12 chromosomes. Phylogenetic analysis divided the IQDs into four subfamilies (IQD I-IV). StIQDs found in three of the four subfamilies. Synteny analysis confirmed that potato and tomato shared a close evolutionary relationship. Besides, RNA-Seq data analysis revealed that the expression of 19 of the 23 StIQDs was detected in at least one of the 12 tissues, and some of which showed a tissue-specific pattern. qRT-PCR results further confirmed that 14 StIQDs responded differently to various abiotic stresses, including drought, extreme temperature, and CaCl2 treatment, suggesting their significance in stress response. This study presents a comprehensive overview of the potato IQD gene family and lays a foundation for further analysis of the StIQDs functions in plant development and stress response.